On the question of the demand for labor in conditions of macroeconomic instability ("Journal "U". Economy. Management. Finance.", 2024)
This article examines some features and factors in the formation and development of labor demand in conditions of macroeconomic instability. Particular attention is paid to its minimum and maximum values.
Keywords: Macroeconomic instability; characteristics and factors of labor demand; maximum and minimum values of labor demand